2001
DOI: 10.1074/jbc.c100487200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Acetyltransferase Found in Saccharomyces cerevisiae Σ1278b That Detoxifies a Proline Analogue, Azetidine-2-carboxylic Acid

Abstract: L-Azetidine-2-carboxylic acid (AZC), a toxic four-membered ring analogue of L-proline, is transported into the cells via proline transporters. It causes misfolding of the proteins into which it is incorporated competitively with L-proline and thereby inhibits the growth of the cells. We recently have discovered, on the chromosome of Saccharomyces cerevisiae ⌺1278b, a novel gene MPR1 required for the resistance of ⌺1278 background strains to toxic AZC. This gene was missing in the particular yeast strain used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 38 publications
(43 reference statements)
0
54
0
Order By: Relevance
“…The yeast haploid strains used in this study are listed in Table 1. The S. cerevisiae strains with a ⌺1278b background were the WT strain L5685 supplied by G. Fink (Massachusetts Institute of Technology, Cambridge) and the mpr-disrupted strain LD1014 (2). Strains L5685Dput1 and L5685Dput2 were constructed from strain L5685.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The yeast haploid strains used in this study are listed in Table 1. The S. cerevisiae strains with a ⌺1278b background were the WT strain L5685 supplied by G. Fink (Massachusetts Institute of Technology, Cambridge) and the mpr-disrupted strain LD1014 (2). Strains L5685Dput1 and L5685Dput2 were constructed from strain L5685.…”
Section: Methodsmentioning
confidence: 99%
“…Although one amino acid change at position 85 occurred between MPR1 and MPR2, both genes are expressed in S. cerevisiae and play similar roles in AZC resistance (1). Gene expression in Escherichia coli and enzymatic analysis showed that MPR1 encodes an AZC acetyltransferase, by which proline itself and other proline analogues are not acetylated (2). The MPR1-encoded protein (Mpr1) is a member of the N-acetyltransferase superfamily (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possible explanations for the AZC resistance of the cells: (i) the cells do not incorporate AZC, suggesting that they possess a different type of amino acid transporter than S. cerevisiae; (ii) the cells accumulate large quantities of L-proline, which dilutes the effect of AZC; 7) and (iii) the cells degrade or modify AZC directly. The hitherto known AZC-resistant strains S. cerevisiae, S. paradoxus, and S. pombe use the third of these mechanisms, because modification of AZC by Mpr1 in these strains eventually converts AZC into Nacetyl-AZC for detoxification, 2,4,5) but, the mechanisms used by the newly identified strains (Table 1) are currently unknown.…”
Section: )mentioning
confidence: 99%
“…1). 2) Homologous genes (Spa MPR1 and ppr1 þ ) that encode similar acetyltransferases have been identified in S. paradoxus, an S. cerevisiae-complex species, 4) and in the fission yeast Schizosaccharomyces pombe, 5) respectively. Moreover, genomic PCR analysis has revealed that most S. cerevisiae-complex species have sequences highly homologous to that of MPR1.…”
mentioning
confidence: 99%